An analysis and study of technical characteristics of the chinese elite open female rowers - Lai, H.; Zheng, W. (Proceedings of the International Conference on Future Computer Science and Education, 2011, 2011)
4 Chinese elite Open-women rowers are chosen, make use of the "Rower Expert Light" (WEBA Sport) to collect the data of 1×rowing technique and analysis. With the increase in tempo, drive and recovery become more rapidly, but push propeller speed increase faster, there is no significant increase in the strength of drive, and the strength of drive for boat speed does not play a decisive role. under the same tempo, less single paddle time, the less ratio of Push and pull will help get faster boat speed. The imbalance of right-left pulling force and the different position of the most strength of drive is appearing will affect the course and speed. In 3 tempo, to 4 athlete, their angle of entry always greater than their angle of release. With the increase in tempo, the angle of hands away no significant change, but bigger the angle of hands away will help increase boat speed. With the increase of tempo, positive acceleration and negative acceleration are increasing too, but range of negative acceleration and the proportion of range of negative acceleration among stroke cycle time decrease which obviously in favour of increase boat speed.